Abdominal cutaneous nerve entrapment syndrome: A cross sectional survey of treatment outcomes. Issue 5 (October 2022) - Kanakarajan, Saravanakumar; Dharmavaram, Sudhindra; Tadros, Amir; Pushparaj, Hemkumar; Rose, Anna
Objective: Abdominal Cutaneous Nerve Entrapment Syndrome (ACNES) is a common but under recognised cause of chronic abdominal wall Pain. This survey was carried out to understand the clinical course of the condition following interventions such as nerve blocks and surgical release of entrapped nerve. Design: Retrospective, Cross-sectional survey. Setting: Pain Management clinic at University teaching hospital. Subjects: Adult patients who had interventions either nerve block or surgical release over a 6 year period. Methods: After written informed consent, participants completed a questionnaire including Brief Pain Inventory (BPI), quality of health measure (EQ-5D-5L), and global impression of change scale as well as open-ended question about the outcomes. Baseline demographics, details of pain condition, interventions received were collected from the health records. Results: The diagnosis of ACNES was established in 85.2% by ultrasound guided injections. The injection therapy with local anaesthetic and steroid was successful to 75.8% while the surgical release was successful in 90%. The cumulative duration of pain relief varied from 3 weeks to 5 years. A significant difference was noted in BPI ( p = 0.001), EQ-5D-5L ( p = 0.002) and health thermometer ( p = 0.009) post interventions. Conclusions: Ultrasound guided injections aid the accurate diagnosis of ACNES. Appropriate treatment of ACNES improves both pain control and quality of life.